Tetrazenyl-, Imido-, and Azidoaluminate Derivatives of a Sterically Demanding Bis-Silazide Ligand - Han-Ying Liu; Ryan J. Schwamm; Jakub Kenar; Mary F. Mahon; Michael S. Hill (Inorganics)
The potassium alumanyl [SiNDippAlK]2 (SiNDipp = {CH2SiMe2NDipp}2; Dipp = 2,6-i-Pr2C6H3) reacts with organic azides via reductive N2 elimination. With the less sterically encumbered azides PhN3 and C10H15N3 (1-azidoadamantane), the putative initially formed aluminium imide undergoes facile [2 + 3] cycloaddition to provide the tetrazenylaluminates [SiNDippAl-κ2-N,N′-({N(R)}2N2)]K (R = Ph, C10H15). In contrast, each Al(I) centre of [SiNDippAlK]2 only reacts with a single equivalent of 2,4,6-Me3C6H2N3 to provide the imidoaluminate [SiNDippAlN(2,4,6-Me3C6H2)(K∙C6H6)], which crystallises as a monomer and displays a short Al-N distance of 1.7040(13) Å. Attempts to synthesise the azide [SiNDippAlN3] by reaction of [SiNDippAlI] with an excess of KN3 resulted in exclusive formation of the bis(azido)aluminate [SiNDippAl(N3)2K], which crystallises as an infinite 1-dimensional polymer propagated by μ-(1,3)-N3 bridging interactions between the potassium cations and azide anions. Although the THF-adducted azide [SiNDippAlN3(THF)] may be synthesised and characterised by more stringent control of the reaction stoichiometry, the synthetic viability of this route remains compromised by competitive generation of [SiNDippAl(N3)2K].